Edukacja – o dwóch metaforach i jednej alegorii słów kilka - Budajczak, Marek (Kultura-Społeczeństwo-Edukacja, 2023)
The essence of education is approached in a number of ways. One of them is the “symbolic approach”. Within that, the said “essence” is depicted using a number of approximations, including: “functional” terms (in which “someone is doing something” or “something is being done to someone”). The subject of reflection in this article are two – seemingly fundamental – educational metaphors, and namely “progress” and “development”, and, additionally, one comprehensive allegory – “education as a ship” after Horace’s Ode 1,14). The aim of the article is to critically analyze the mentioned symbolic expressions using etymology, and so the method of conducting this research is the method of etymological explications. The main conclusion of the article is a warning against thoughtless use of metaphors in the language of educational sciences.